Impact of Lyophilisation on Integrity of Structural and Functional Characteristics of Human Cord Blood Leukoncentrate - Koval, Ganna K.; Lutsenko, Olena D.; Grisha, Igor G.; Sokil, Larisa V.; Bondarovych, Mykola O.; Ostankov, Maksim V.; Yampolskaya, Kateryna Ye.; Ostankova, Lyudmila V.; Goltsev, Anatoliy M. (Problems of Cryobiology and Cryomedicine, 2019)
This paper presents the investigations on the impact of lyophilisation conditions on structural and functional characteristics of human cord blood leukoconcentrate (HCBL) such as: the number and viability, cytomorphological indices, content of hematopoietic stem (CD34+) and T-regulatory cells (CD4+CD25high), hematopoietic colony forming units in culture (CFUc). Four regimens, including two programs with and without 3.5% DMSO were used for hcbl cell lyophilisation. The programs diï¬€ered in temperature value and duration wherein the primary drying proceeded. When using the ï¬rst program, the cells were dried for 10 hrs (â€“28ÂºÐ¡), and 9 hrs (â€“18ÂºÐ¡) for the second one. The designed method for HCBL lyophilisation, suggested the use of the DMSO-free ï¬rst program, ensured the cell preservation in a heterogeneous population of cord blood according to all the studied characteristics. Â Probl Cryobiol Cryomed 2019; 29(4):Â 332-343